Determining the optimal public debt threshold for Nigeria - Babatunde S. Omotosho; Sani Bawa; Sani I. Doguwa (CBN Journal of Applied Statistics, 2016)
This paper investigates the existence of threshold effects in the relationship between public debt and economic growth in Nigeria using quarterly data. Generally, we found empirical support for an inverted U-shape relationship between public debt types and economic growth. For total public debt as percentage of GDP, model results identified a threshold level of 73.70 per cent, while the estimated inflexion points for external and domestic debts were 49.4 and 30.9 per cent, respectively. The implication of this finding is that debt accumulation in excess of the estimated threshold levels could hurt economic growth. A retrospective examination of the country's total and external debts profile indicated that the estimated threshold levels were exceeded prior to the debt forgiveness negotiated in 2005 and largely within limits afterwards. In addition, the study found empirical support for external debt accumulation opportunities, however, we caution that such additional debt incurrence be done in a manner that is consistent with the country's growth objectives.
Keywords: F34; E62; H62; H63; 330; Public Debt; Economic Growth; Threshold Effects